Penerapan Trichoderma Meningkatkan Kualitas Air Tambak di Desa Pao, Luwu Utara - Ishak Nurlang; Suherah Saleh; Arianto Dangkeng; Imelda Iskandar; Azniah Syam (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Traditional pond aquaculture often struggles with declining water quality due to feed waste accumulation and chemical use. Trichoderma, a saprophytic fungus widely known as a biological control agent, offers an environmentally friendly alternative for improving pond conditions. This article reports a community service program in Pao Village, North Luwu, where liquid Trichoderma was applied in traditional ponds and its impact on water quality was evaluated. Activities included training local farmers in fungal propagation and inoculum application for whiteleg shrimp and milkfish culture. Laboratory tests of water quality parameters were conducted before and one month after application. Results showed notable improvements: pH increased from 6.8 to 7.0, ammonia decreased from 0.2322 to 0.2119 mg/L, nitrite dropped from 0.0751 to 0.0174 mg/L, and total phosphate declined by approximately 29%. Water clarity also improved as total suspended solids decreased from 11 to 9 mg/L, while dissolved oxygen remained stable (5.71–5.53 mg/L). These findings demonstrate that Trichoderma effectively stabilizes pond ecosystems by reducing toxic compounds and maintaining favorable conditions for aquaculture. The intervention not only supports sustainable and eco-friendly aquaculture practices but also empowers local farmers to reduce dependency on chemicals and antibiotics, ultimately enhancing productivity and contributing to food security.